Implementation of e-government in Malawi - MWAMBIWA, Stallichi Ishmael (KDI School, 2016)
The advent of e-government in most developing countries was considered as a panacea to enhance efficiency and effectiveness in the delivery of public services. Similarly, most proponents of the initiative envisioned the potential for developing countries to create an enabling environment for the growth of the private sector and harmonization of information across government departments and agencies. Like many developing countries, Malawi adopted the initiative in the early 2000 with the triple goal of enhancing service delivery, growth of the private sector and information sharing between and among government agencies. This study explored the implementation of e-government in Malawi from its inception in 2004. The results reveal that the implementation of e-government in Malawi has not been as successful as espoused by the proponents. The study established several challenges that have hampered the successful implementation of e-government in Malawi which include lack of political will, change management problems, lack of proper coordination with other stakeholders, cultural impacts as well as the general lack of policy direction. The study has also revealed, through a policy comparative analysis with Mozambique, that Malawi lags behind in the initiative owing to lack of proper strategic interventions such as ICT and E-government Implementation Strategies that provide a general direction on the adoption and operationalization of the e-government initiative in government departments and agencies with specific targets, time frame and deliverables for evaluation The study, therefore, has put in place several recommendations for the successful implementation of e-government in Malawi to enable the country to realize the benefits of the initiative. These recommendations include the development of the ICT and E-government Implementation Strategies, enacting regulatory policies to support e-government implementation, instituting sound e-government awareness programs, revisiting the existing curricula for government training institutions to accommodate ICT programs, incentivizing existing e-services to lure more users and establishing the e-government advisory committee that will comprise both key government officials and the private sector operators. In overall, these recommendations ameliorate existing e-government implementation challenges in Malawi and ultimately, provide profound opportunities for the success of e-government implementation in the country.
Thesis(Master) --KDI School:Master of Public Management,2016